Cena mleka i jego przetworów w Polsce jako czynnik ich konkurencyjności - Gornowicz, Mirosław (Prices of Milk and Milk Products in Poland as An Element of Their Competitiveness, 2005)
Until quite recently price was the most important factor positively affecting the competitive power of Polish dairy products on the European Union market. The price of finished products depends to the highest extent on the price of raw materials. In 2002 and 2003 the average price of milk in Poland accounted for 60.9% and 55.2% respectively of the mean price of milk in the EU. Due to a significant increase in milk prices recorded in Poland in 2004, and strengthening of Polish zloty in relation to euro, in July 2004 the price of milk in Poland was lower by only about 25% than in Great Britain. As a result, the differences in prices of milk products between the Polish and EU markets became much smaller. In December 2004 the price of skimmed milk powder was higher in Poland than in Great Britain, and the price of milk was by only several percent lower in Poland than in Great Britain, Germany, France or the Netherlands. Due to this direction of changes, the role of price as a factor deciding about the competitiveness of Polish dairy products on the EU market is gradually diminishing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 272-276